2019
DOI: 10.1038/s41598-019-51078-z
|View full text |Cite
|
Sign up to set email alerts
|

Morphological evidence for telocytes as stromal cells supporting satellite cell activation in eccentric contraction-induced skeletal muscle injury

Abstract: Although telocytes (TCs) have been proposed to play a “nursing” role in resident satellite cell (SC)-mediated skeletal muscle regeneration, currently there is no evidence of TC-SC morpho-functional interaction following tissue injury. Hence, we explored the presence of TCs and their relationship with SCs in an ex vivo model of eccentric contraction (EC)-induced muscle damage. EC-injured muscles showed structural/ultrastructural alterations and changes in electrophysiological sarcolemnic properties. TCs were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(65 citation statements)
references
References 65 publications
6
59
0
Order By: Relevance
“…However, among other procedures, ultrastructural studies have clearly demonstrated that TCs are different from fibroblasts [ 1 , 2 , 3 ]. Likewise, it is widely accepted that cells ultrastructurally identifiable as TCs largely correspond to the CD34+ stromal cells (TCs/CD34+SCs) observed in light microscopy [ 43 ].…”
Section: General Characteristics Of Telocytes and Terminological Imentioning
confidence: 99%
“…However, among other procedures, ultrastructural studies have clearly demonstrated that TCs are different from fibroblasts [ 1 , 2 , 3 ]. Likewise, it is widely accepted that cells ultrastructurally identifiable as TCs largely correspond to the CD34+ stromal cells (TCs/CD34+SCs) observed in light microscopy [ 43 ].…”
Section: General Characteristics Of Telocytes and Terminological Imentioning
confidence: 99%
“…A new cellular type named telocyte was identified by electron microscopy and described in 2010 (Popescu and Faussone-Pellegrini, 2010; Faussone Pellegrini and Popescu, 2011;Popescu, 2011). This cell type largely corresponds to the CD34+ stromal cells observed in light microscopy (Rusu et al, 2016;Manetti et al, 2019). Several roles have been hypothesized for CD34+ stromal cells/telocytes (CD34+SCs/TCs) in (a) the maintenance and modulation of tissue homeostasis, including organization and control of the extracellular matrix, structural support, creation of microenvironments, integration of tissue components, control and regulation of other cells, and immunomodulation (Faussone Pellegrini and Popescu, 2011;Popescu, 2011;Popescu and Nicolescu, 2013;Díaz-Flores et al, 2014, 2016aCretoiu et al, 2016Cretoiu et al, , 2020 regeneration and repair (Faussone Pellegrini and Popescu, 2011;Popescu, 2011;Popescu et al, 2011;Ceafalan et al, 2012;Bani and Nistri, 2014;Díaz-Flores et al, 2015a,b, 2016b.…”
Section: Introductionmentioning
confidence: 75%
“…Several roles have been hypothesized for CD34+ stromal cells/telocytes (CD34+SCs/TCs) in (a) the maintenance and modulation of tissue homeostasis, including organization and control of the extracellular matrix, structural support, creation of microenvironments, integration of tissue components, control and regulation of other cells, and immunomodulation ( Faussone Pellegrini and Popescu, 2011 ; Popescu, 2011 ; Popescu and Nicolescu, 2013 ; Díaz-Flores et al, 2014 , 2016a ; Cretoiu et al, 2016 , 2020 ; Vannucchi et al, 2016 ) regeneration and repair ( Faussone Pellegrini and Popescu, 2011 ; Popescu, 2011 ; Popescu et al, 2011 ; Ceafalan et al, 2012 ; Bani and Nistri, 2014 ; Díaz-Flores et al, 2015a,b , 2016b ; Vannucchi et al, 2016 ). In regeneration, CD34+SCs/TCs act on neighboring parenchymal stem cells, regulating their proliferation and maturation ( Faussone-Pellegrini and Bani, 2010 ; Popescu, 2011 ; Ceafalan et al, 2012 ; Gherghiceanu and Popescu, 2012 ; Rusu et al, 2016 ; Vannucchi and Faussone-Pellegrini, 2016 ; Cretoiu et al, 2017 ; Manetti et al, 2019 ). In repair through granulation tissue, CD34+SCs/TCs play an important role as precursor cells.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the ability of TCs to form complex interstitial networks and communicate with neighboring cells by establishing multiple intercellular contacts or releasing extracellular vesicles containing bioactive molecules, together with the evidence that such TC networks are severely impaired in a variety of pathologies, led to proposing that these cells may exert a wide spectrum of functions important for the maintenance of tissue homeostasis [ 2 , 4 , 5 , 10 , 28 , 29 , 57 , 58 ]. For instance, owing to their strategic position in relation to tissue-resident stem cell niches in various organs and satellite cells in the skeletal muscle, it has been postulated that TCs may play a pivotal role in stem cell survival, proliferation, differentiation, maturation, and guidance, eventually stimulating tissue regenerative processes [ 5 , 19 , 52 , 59 , 60 , 61 , 62 ]. Furthermore, TCs are usually found to intimately surround microvessels with their telopodes and may express proangiogenic growth factors, such as vascular endothelial growth factor, and several microRNAs with angiogenic functions, suggesting that they may influence EC functions contributing to vascular homeostasis and neovascularization processes [ 41 , 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%